The lived experience of sustainable learning: the Lech-e OER project bridging formal and non formal lifelong learners - Teixeira, António (2011)
The Erasmus-funded Lived experience of climate change: e-learning and virtual mobility (LECH-e) project is developing learning resources on the topic of climate change that will be openly accessible on the web for higher education institutions and the wider world public to use and adapt. Institutions are free to integrate the resources into their formal programs and non-formal courses. A description of the project is provided in a short prologue. In this paper we depict the open learning strategy implemented by the LECH-e partnership and how it can contribute to widening participation in environmental, and specifically climate change, education.